Analyzing barriers for implementation of public health and social measures to prevent the transmission of COVID-19 disease using DEMATEL method. Issue 5 (September 2020) - Maqbool, Annayath; Khan, Noor Zaman
Abstract: Background and aims: COVID-19 is a contagious disease caused by a new coronavirus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Till now there are no vaccines and explicit medicines available for the treatment of COVID-19 disease, therefore the initiatives like public health and social measures are helpful in limiting the quantity of contaminations and saving lives. Keeping this in view, an attempt has been made in the present work to identify the barriers which hinder the implementation of these public health and social measures Methods: The barriers to implement public health and social measures for preventing transmission of COVID-19 are identified using systematic literature review and these barriers are then categorized using Decision-making trial and evaluation laboratory (DEMATEL) method. Results: Results reveal that among ten identified barriers, Lack of resources for implementing public health and social measures is found to be the most influential barrier to implement public health and social measures for preventing transmission of COVID-19. Conclusions: The successful implementation of public health and social measures depends on the adequate availability of resources which include medical equipment, personnel and financial dealings. The outcome of this research work will benefit and motivate the higher authorities to consider and overcome various challenges to prevent the transmission of COVID-19. Highlights: This paper identifies important barriers related to the prevention of COVID-19 and categorizes them using DEMATEL method. Lack of resources is found to be the most influential barrier. Some future research directions are given to prevent transmission of COVID-19.